New correlations between uniaxial compressive strength and point load strength of basalt. Issue 4 (September 2015) - Endait, M.; Juneja, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Although the mechanical and physical properties of many rocks have extensively been studied, little work is reported on basalt rock. This paper discusses the interrelationships between the mechanical and the physical properties of the basalt rock. Laboratory tests were conducted on rock cores collected from over 22 locations within the Mumbai city limits. The samples were tested in accordance with ISRM (1985) specifications. Correlations between the uniaxial compressive strength (UCS) and the point load strength index (Is.50) were developed. It was observed that other than the customary linear relations and power function between UCS and Is.50, a bilinear relation best fitted the laboratory data.